HGG-37. UPFRONT TARGETED THERAPY FOR THE TREATMENT OF BRAFV600E-MUTANT PEDIATRIC HIGH-GRADE GLIOMA – A MULTI-INSTITUTIONAL EXPERIENCE. (1st June 2021) - Rosenberg, Tom; Yeo, Kee Kiat; Joshirao, Mrinal; Michaiel, George; Tran, Hung; Dahiya, Sonika; Kachurak, Kara; Friedman, Gregory; Huang, Michael; Wright, Karen; Aguilera, Dolly; MacDonald, Tobey; et al.
Abstract: Introduction: Sustained responses to molecular targeted therapy with BRAF with or without MEK inhibitors have been reported in patients with recurrent BRAFV600E-mutant pediatric high-grade gliomas (pHGG). The role of upfront targeted therapy in this population, however, has not yet been established. Methods: We performed a retrospective, multi-institutional record review of patients with BRAFV600E-mutant pHGGs, treated with off-label BRAF and/or MEK inhibitors as part of their initial adjuvant therapy. Results: Seventeen patients were identified (median age at diagnosis, 8.8 years, range 1.8–20.2). Histologic diagnoses included HGG/glioblastoma (n=10), anaplastic ganglioglioma (n=3), high-grade neuroepithelial tumor (n=2), diffuse midline glioma (n=1) and anaplastic astroblastoma (n=1). Ten patients underwent biopsy (n=8) or subtotal resection (n=2), while near-total or complete resection was accomplished in seven. Concomitant genetic alterations including CDKN2A/B loss, H3K27M and TERT promotor mutations were found in eight tumors. Thirteen patients received focal radiation therapy (RT) and one received craniospinal irradiation prior to targeted therapy. Adjuvant targeted therapy was initiated shortly after diagnosis or completion of RT. Five patients received BRAF-inhibitor monotherapy (dabrafenib or vemurafenib). Twelve patients received combination therapy with the addition of a MEK inhibitor (trametinib). For patients with measurable disease, best responses per COG criteria were CR (n=3), PR (n=7), SD (n=3) and PD (n=1). With median follow-up of 29 months (range 8–78), two-year PFS and OS for the cohort were 74.7% and 81.1%, respectively. Ten (59%) patients remain free of disease recurrence or progression. Grade 3 or higher toxicities were reported in four patients (neutropenia, skin toxicity/photosensitivity, fatigue and weight loss), leading to therapy discontinuation in two. Conclusions: Upfront targeted therapy for patients with BRAFV600E mutant pHGG appears tolerable and effective, with a durable disease control rate that is superior to historical data. This promising paradigm is currently being evaluated prospectively in the COG ACNS1723 clinical trial.